Genome-wide analysis of histone acetyltransferase and histone deacetylase families and their expression in fruit development and ripening stage of pepper (Capsicum annuum) - Cai, Yutong; Xu, Mengwei; Liu, Jiarong; Zeng, Haiyue; Song, Jiali; Sun, Binmei; Chen, Siqi; Deng, Qihui; Lei, Jianjun; Cao, Bihao; Chen, Changming; Chen, Muxi; et al. (Frontiers in Plant Science, 2022)
The fruit development and ripening process involve a series of changes regulated by fine-tune gene expression at the transcriptional level. Acetylation levels of histones on lysine residues, are dynamically regulated by histone acetyltransferases (HATs) and histone deacetylases (HDACs), which play an essential role in the control of gene expression. However, their role in regulating fruit development and ripening process, especially in pepper (Capsicum annuum), a typical non-climacteric fruit, remains to understand. Herein, we performed genome-wide analyses of the HDAC and HAT family in the pepper, including phylogenetic analysis, gene structure, encoding protein conserved domain and expression assays. A total of 30 HAT and 15 HDAC were identified from the pepper genome, and the number of gene differentiation among species. The sequence and phylogenetic analysis of CaHDACs and CaHATs compared with other plant HDAC and HAT proteins revealed gene conserved and potential genus-specialized genes. Furthermore, fruit developmental trajectories expression profiles showed that CaHDAC and CaHAT genes were differentially expressed, suggesting that some are functionally divergent. The integrative analysis allowed us to propose CaHDAC and CaHAT candidates to be regulating fruit development and ripening-related phytohormone metabolism and signalling, which also accompanied capsaicinoid and carotenoid biosynthesis. This study provides new insights into the role of histone modification mediate development and ripening in non-climacteric fruits.